Depot medroxyprogesterone acetate and epithelial ovarian cancer: A multicentre case-control study - Wilailak S. (2017)
Objective To evaluate the effect of depot medroxyprogesterone acetate (DMPA) in protecting against epithelial ovarian cancer (EOC) and to evaluate factors associated with the risk of EOC. Design A multicentre, case-control study. Setting Twelve hospitals located across Thailand. Population Three hundred and thirty patients with EOC ('cases') and 982 matched controls were recruited from the 12 hospitals. Cases were newly diagnosed patients with EOC, demonstrated pathologically. Controls were age-matched patients admitted to different wards in the same hospital. Methods Cases and controls were interviewed by trained interviewers using a standardised pre-tested questionnaire. The factors associated with EOC were evaluated using univariate and multivariate analyses. Main outcome measures The odds ratio (OR) and 95% confidence interval (95% CI) were calculated to assess the relationship between DMPA and EOC. Results The use of DMPA was found to be associated with a 39% reduction in the risk of EOC with an OR of 0.61 and a 95% CI of 0.44-0.85 (P = 0.002). A significant risk reduction (83%) was observed when the duration of DMPA use was > 3 years (OR 0.17; 95% CI 0.07-0.39; P < 0.001). Other factors associated with a reduced risk of EOC were the use of combined oral contraceptive pills and breastfeeding. A factor associated with an increased risk of EOC was a family history of gynaecological cancer. Conclusions The results suggest that DMPA may have a protective effect against EOC. If this effect is real, then it represents an important non-contraceptive benefit of DMPA. © 2012 RCOG.